2009
DOI: 10.1111/j.1524-4725.2008.34399.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Fractional Photothermolysis System with Dynamic Operating Mode on Acne Scars and Enlarged Facial Pores

Abstract: We suggest that the FPS may provide a new treatment algorithm in some cases with acne scars and enlarged pores. Considering the lack of placebo-controlled, split-face design of our study, optimized, prospective studies should be conducted to fully assess the efficacy of FPS with dynamic operating mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 21 publications
(43 reference statements)
3
70
0
1
Order By: Relevance
“…5 In the same study, the 1,550-nm fractional Er:glass fiber lasers effectively induced rearrangement of collagen fibers and stimulation of new collagen production. 5 Meanwhile, ablative 10,600-nm fractional carbon dioxide lasers have been found to elicit superior effects in tissue shrinkage and increased elasticity, compared to fractional Er:glass fiber lasers.…”
Section: Case Reportmentioning
confidence: 88%
See 2 more Smart Citations
“…5 In the same study, the 1,550-nm fractional Er:glass fiber lasers effectively induced rearrangement of collagen fibers and stimulation of new collagen production. 5 Meanwhile, ablative 10,600-nm fractional carbon dioxide lasers have been found to elicit superior effects in tissue shrinkage and increased elasticity, compared to fractional Er:glass fiber lasers.…”
Section: Case Reportmentioning
confidence: 88%
“…5 In the same study, the 1,550-nm fractional Er:glass fiber lasers effectively induced rearrangement of collagen fibers and stimulation of new collagen production. 5 Meanwhile, ablative 10,600-nm fractional carbon dioxide lasers have been found to elicit superior effects in tissue shrinkage and increased elasticity, compared to fractional Er:glass fiber lasers. 2,4 However, considering the pain during the procedure, post-therapy downtime, and the risks of post-inflammatory dyspigmentation and erythema with ablative fractional carbon dioxide lasers, fractional Er:glass fiber lasers are preferred when treating atrophic scars of various origins.…”
Section: Case Reportmentioning
confidence: 88%
See 1 more Smart Citation
“…We suggested that the multiple movement patterns of the moving-operating mode enabled us to effectively treat large areas (5). Additionally, random spray shots on stamp and moving operating mode seemed to reduce the laser therapyassociated pain as well as thermal damages to surrounding tissues.…”
Section: Treatment Of Infl Ammatory Acne With V Beam and Fps 177mentioning
confidence: 99%
“…hafif ve orta şiddette akne skarları olan 12 hastaya fraksiyonel lazer tedavisi uygulamış ve çalışmada genişlemiş porların iyileşme oranları da değerlendirilmiştir. Değerlendirmede yüzdeki genişlemiş porların 12 hastanın 6'sında %50'nin üzerinde küçüldüğü gösterilmiştir 13 . Yakın gelecekte, yüzdeki genişlemiş porlar akne skarları gibi dermatolojik hastalıklar sınıfında değerlendirilerek yeni tedavi yöntemleri üzerinde durulacağı değerlendirilmektedir.…”
unclassified